The Relationship Between Duration of Playing Online Games With Tear Film Stability on Student of the Faculty of Medicine, University of Nusa Cendana - Bintang Musa Bessie (Cendana Medical Journal, 2025)
Background : Dry eye which is affected by the duration of staring at screens such as playing online games. Purpose : To determine the relationship between the duration of playing online games with tear film stability in medical students. Methods :an observational analytic study with a cross sectional. The data was obtained by conducting a TBUT (Tear Break Up Time Test) examination by an ophthalmologist. Results : Sample playing online games for < 2 hours a day , samples with marginal evaporated dry eye and 10 (20%) samples with normal tear film stability. A total of 24 samples who played online games with a duration of 2-5 hours a day were 12 (24%) samples with marginal evaporated dry eye and 12 (24%) samples with normal tear film stability. A total of 8 (16%) samples who played online games with a duration of > 5 hours, there were 5 (10%) samples with marginal evaporated dry eye and 3 (6%) with normal tear film stability. The results of the somers'd correlation analysis test showed a significance level of p = 0.424 (p> 0.05). Conclusion : There is no significant relationship between the duration of playing online games with tear film stability.